Acute pediatric peritoneal dialysis: impact of an opt-out model and adaptable methods in a hospital in Nigeria (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Despite efforts to scale peritoneal dialysis (PD) uptake, access is still limited in Sub-Saharan Africa, including Nigeria. Thus, this study evaluated access to PD, cost-effectiveness, complications, and in-hospital mortality rate following the adoption of a local opt-out model approach for all children with acute kidney injury (AKI) that required PD. METHODS This work was a retrospective review of 33 children with AKI that required dialysis between December 2014 and November 2016. PD was carried out using locally adaptable consumables in place of commercially produced consumables. All patients that required renal replacement therapy (RRT) were offered an option to opt-out irrespective of their financial status. Patients’ relevant data were retrieved from the case notes and analyzed. RESULTS The median age was 7 years (range 3–12). 23 patients (70%) were males. Of the 33 patients that required RRT, 29 had PD. The children had an access rate of 88% (95% CI = 76.77–99.03). The access rate was not related to gender (p = 1.000), age group (p = 0.240), or socioeconomic status (p = 0.755). Complications were pericatheter leakage of fluid (n = 7, 24%), catheter malfunction (n = 5, 17%), abdominal wall edema (n = 3, 10%), scrotal edema (n = 2, 7%), and peritonitis (n = 1, 3%). In-hospital mortality was 3/29 (10%; 95% CI = 2.2–27.3). Cost analysis revealed that the cost of consumables was reduced by 88.5%. CONCLUSIONS An opt-out model with the use of locally adaptable consumables improved PD access (88%) with a low in-hospital mortality rate.